Effect of Lactobacillus fermentum HFY03 on the Antifatigue and Antioxidation Ability of Running Exhausted Mice. (28th September 2021) - Zhang, Junxiao; Chen, Ling; Zhang, Lingyan; Chen, Qiuping; Tan, Fang; Zhao, Xin
Abstract : Yak yogurt is mainly produced in Qinghai-Tibet Plateau. It is a kind of naturally fermented dairy product. It contains abundant microorganisms. Lactobacillus fermentum (LF) HFY03 is a lactic acid bacteria derived from it. Our main research content is to study the influence of LF-HFY03 on the antifatigue and antioxidation ability of running exhausted mice. We gave different doses of LF-HFY03 to mice by gavage for 4 weeks. We selected vitamin C as the positive control group, mainly to study the relationship between antioxidant capacity and fatigue resistance and LF-HFY03 in mice with running exhaustion. The results showed that LF-HFY03 and vitamin C could significantly improve the running time of mice. And with the increase in LF-HFY03 concentration, the exhaustion time of mice was also extended. LF-HFY03 can reduce the content of urea nitrogen and lactic acid and also can increase the content of free fatty acids and liver glycogen. The levels of alanine aminotransferase, serum creatine kinase, and aspartate aminotransferase in mice decreased gradually as the antioxidant peptide level of walnut albumin increased. LF-HFY03 can reduce malondialdehyde (MDA) levels in a quantification-dependent manner and can also increase catalase (CAT) and superoxide dismutase (SOD) levels. LF-HFY03 can also increase the expressions of CAT mRNA, Cu/Zn-SOD, and Mn-SOD in the liver of mice. At the same time, LF-HFY03 can also increase the expression of protein of threonine transporter 1 (AST1)/alanine/cysteine/serine, mRNA, nNOS, and eNOS. At the same time, the solution could reduce the expression of TNF- α, syncytin-1, and inducible nitric oxide synthase (iNOS). The results showed that LF-HFY03 has a high development and application prospect as an antifatigue probiotic nutritional supplement.